Water Model Study on Removing Inclusion from Molten Steel by Bubble Attachment in RH Degasser - Chunjie Yang; Fuping Tang; Minggang Shen (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
In this paper, a water model is established, at geometric similarity ratio of 1:4, to simulate a real 180-t RH vacuum refining device. Removing inclusion from molten steel by bubble attachment in RH degasser is analyzed using the water model. The effects of variables such as bubble size, treatment time, life-gas flow rate, amount and time of NaHCO3 addition are investigated by using high speed video and image-process software.